2006
DOI: 10.1128/jb.188.4.1466-1472.2006
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Charged Residues of Rotor and Stator in Flagellar Rotation: Comparative Study using H + -Driven and Na + -Driven Motors in Escherichia coli

Abstract: In Escherichia coli, rotation of the flagellar motor has been shown to depend upon electrostatic interactions between charged residues of the stator protein MotA and the rotor protein FliG. These charged residues are conserved in the Na ؉ -driven polar flagellum of Vibrio alginolyticus, but mutational studies in V. alginolyticus suggested that they are relatively unimportant for motor rotation. The electrostatic interactions detected in E. coli therefore might not be a general feature of flagellar motors, or, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
87
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

6
3

Authors

Journals

citations
Cited by 79 publications
(92 citation statements)
references
References 32 publications
0
87
0
Order By: Relevance
“…In the H ϩ -driven motors of E. coli, it is inferred that the conserved charged residues of FliG and MotA interact, which is important for torque generation (26,33). Mutation of the cytoplasmic domain at L131 and T132 in PomA affects the temperature sensitivity of the mutants at the conserved charged residues of PomA (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the H ϩ -driven motors of E. coli, it is inferred that the conserved charged residues of FliG and MotA interact, which is important for torque generation (26,33). Mutation of the cytoplasmic domain at L131 and T132 in PomA affects the temperature sensitivity of the mutants at the conserved charged residues of PomA (6).…”
Section: Discussionmentioning
confidence: 99%
“…In the H ϩ -driven motor of E. coli, it has been shown that charged residues of MotA and FliG are important for torque generation (26,33). On the other hand, the Na ϩ -driven motor of V. alginolyticus may not require the corresponding charged residues for torque generation (29,31).…”
mentioning
confidence: 99%
“…FliG, 26 molecules of which are incorporated into the motor, appears to be the protein that is most directly involved in torque generation (15). Mutational analysis suggests that electrostatic interactions between conserved charged residues in the C-terminal domain of FliG and the cytoplasmic domain of MotA are important in torque generation (14), although this may not be the case for the Na ϩ -type motor of Vibrio alginolyticus (32,35,36). FliM interacts with the chemotactic signaling protein CheY in its phosphorylated form (CheY-P) to regulate rotational direction (30).…”
mentioning
confidence: 99%
“…Using this chimeric motor system, a comparative study was carried out with E. coli (29). Neutral or charge reversal mutations were introduced into conserved charged residues in the cytoplasmic domain of PomA and the C terminus of FliG from V. alginolyticus.…”
mentioning
confidence: 99%